QUICK RESPONSE CODE INDONESIA STANDARD (QRIS) SEBAGAI STRATEGI SURVIVE USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI MASA PANDEMI DI KOTA KEDIRI - Sri Anugrah Natalina; Arif Zunaidi; Risa Rahmah (Istithmar: Jurnal Studi Ekonomi Syariah, 2021)
One of the impacts of this pandemic is MSME actors who must be prepared for new consumer patterns and behaviors. Adaptation to technological advances must be carried out by MSME actors to be able to survive. Bank Indonesia as Indonesia's central bank made a breakthrough to use QRIS as a way for MSMEs to survive this pandemic. The results of this study were tested using a qualitative approach, with interviewers for MSME actors represented by 5 (five) MSME actors in each sub-district in the city of Kediri. The benefits obtained from QRIS are convenience for transactions with consumers without using cash, and being able to easily implement health protocols with consumers. Meanwhile, the obstacles that occur are internet connectivity that is not smooth, data costs are quite expensive and the perpetrators are not confident. From the Department of Cooperatives and SMEs of Kediri City, there have been many policies that have been carried out to be able to support the suvive of SMEs in Kediri, namely the existence of training and the existence of cooperatives for SMEs. And QRIS in Kediri City showed that as many as 53% expressed interest in using QRIS for their trade transactions.